Incidence of Preclinical Heart Failure in a Community Population - Kathleen A. Young; Christopher G. Scott; Richard J. Rodeheffer; Horng H. Chen (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background A high prevalence of preclinical heart failure (HF) (Stages A and B) has previously been shown. The aim of this study was to explore factors associated with the incidence of preclinical HF in a community population. Methods and Results Retrospective review of 393 healthy community individuals aged ≥45 years from the Olmsted County Heart Function Study that returned for 2 visits, 4 years apart. At visit 2, individuals that remained normal were compared with those that developed preclinical HF. By the second visit, 191 (49%) developed preclinical HF (12.1 cases per 100 person‐years of follow‐up); 65 (34%) Stage A and 126 (66%) Stage B. Those that developed preclinical HF (n=191) were older (P=0.004), had a higher body mass index (P<0.001), and increased left ventricular mass index (P=0.006). When evaluated separately, increased body mass index was seen with development of Stage A (P<0.001) or Stage B (P=0.009). Echocardiographic markers of diastolic function were statistically different in those that developed Stage A [higher E/e’ (P<0.001), lower e’ (P<0.001)] and Stage B [higher left atrial volume index (P<0.001), higher E/e’ (P<0.001), lower e’ (P<0.001)]. NT‐proBNP (N‐terminal pro‐B‐type natriuretic peptide) was higher at visit 2 in those that developed Stage A or B (P<0.001 for both). Hypertension (57%), obesity (34%), and hyperlipidemia (25%) were common in the development of Stage A. Of patients who developed Stage B, 71% (n=84) had moderate or severe diastolic dysfunction. Conclusions There is a high incidence of preclinical HF in a community population. Development of Stage A was driven by hypertension and obesity, while preclinical diastolic dysfunction was seen commonly in those that developed Stage B.